NaCl salinity enhances tetracycline bioavailability to Escherichia coli on agar surfaces. (September 2022) - Chen, Zeyou; Yin, Lichun; Zhang, Wei; Peng, Anping; Sallach, J. Brett; Luo, Yi; Li, Hui
Abstract: Soil salinity is a worldwide problem and is damaging soil functions. Meanwhile, increasing amounts of anthropogenic antibiotics are discharged to agricultural soils. Little is known about how soil salinity (e.g., NaCl) could influence the bioavailability of antibiotics to bacteria. In this study, a tetracycline-responsive Escherichia coli bioreporter grew on the surfaces of agar microcosms at the same tetracycline concentration (200 μg/L), but various NaCl concentrations (0.5–19.2 g/L) with estimated osmotic potential of −0.18 to −1.80 MPa, and agar content (0.3%–5%) with estimated intrinsic permeability of 38 to 32, 928 nm 2 . These agar microcosms mimicked very fine textured soils with a range of NaCl salinity. Increasing agar content lowered the intrinsic permeability hence decreasing tetracycline bioavailability to E. coli, due likely to the reduced mass transfer of tetracycline via water flow. Intriguingly, tetracycline bioavailability increased with increasing NaCl concentration which caused the increase in osmotic stress. This is contradictory to the notion that osmotic stress reduces bacterial chemical uptake. Further analysis of E. coli membrane integrity demonstrated that the enhanced tetracycline bioavailability to bacteria could result from the compromised cell membranes and enhanced membrane permeability at higher NaCl salinity. Overall, this study suggests that high soil salinity (NaCl) may enhance the selection pressure exerted by antibiotics on bacteria. Graphical abstract: Image 1 Highlights: Increasing matrix intrinsic permeability reduced tetracycline bioavailability. NaCl salinity enhances tetracycline bioavailability to bacteria. Increased soil salinity could promote the development of antibiotic resistance.